Design, formulation and implementation of an English Language curriculum fom an Islamic Perspective - Ahamed Shah, Mohamed Ismail; Muhamad, Ainon Jariah; Mohamed Ismail, Shahar (International Islamic University Malaysia, 2012)
Curriculum development plays an important role in any educational enterprise.It spells out the crucial components which make up the curriculum and the detailed process in attaining the ultimate objectives of the curriculum. It is crucial that the English language curriculum reflects the aims, educational purpose and Islamic ethos of the International Islamic University Malaysia (IIUM). The paper will look into how to accomplish the philosophy, vision and mission of the University, offering suggestions concerning the key components or critical elements that will constitute the foundation of a language curriculum, with a focus on the role of the educator in facilitating language education as well as content factors that are necessary for the development of a language curriculum from an Islamic perspective.